1981
DOI: 10.1172/jci110230
|View full text |Cite
|
Sign up to set email alerts
|

In vitro reversal of the fasting state of liver metabolism in the rat. Reevaluation of the roles of insulin and glucose.

Abstract: A B S T R A C T Studies were conducted to determine whether the direction ofhepatic carbohydrate and lipid metabolism in the rat could be switched simultaneously from a "fasted" to a "fed" profile in vitro. When incubated for 2 h under appropriate conditions hepatocytes from fasted animals could be induced to synthesize glycogen at in vivo rates. There was concomitant marked elevation of the tissue malonyl-coenzyme A level, acceleration of fatty acid synthesis, and suppression of fatty acid oxidation and ketog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
2

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(81 citation statements)
references
References 40 publications
(43 reference statements)
5
74
0
2
Order By: Relevance
“…There was no accumulation of glycogen in these cells during incubation in agreement with other reports studying hepatocytes incubated with glucose [23][24][25].…”
Section: Discussionsupporting
confidence: 93%
“…There was no accumulation of glycogen in these cells during incubation in agreement with other reports studying hepatocytes incubated with glucose [23][24][25].…”
Section: Discussionsupporting
confidence: 93%
“…Malonyl-CoA-mediated inhibition of carnitine palmitoyltransferase represents a mechanism by which mitochondrial oxidation of long-chain fatty acids is regulated (29). As malonyl-CoA is the enzyme product of acetyl-CoA carboxylase, its concentration in the liver proportionally decreases as the rate of fatty acid synthesis decreases (30). Thus, depression by soybean phospholipid of hepatic fatty acid synthesis should decrease the malonyl-CoA concentration in the liver and in turn enhance the rate of fatty acid oxidation even when the activities of the If the depression of fatty acid synthesis is a factor primarily responsible for the lipid-lowering effect of soybean phospholipid(1-9), the lipid-lowering effect of the phospholipid should be diminished under the condition in which hepatic fatty acid synthesis is hampered.Dietary polyunsaturated fatty acids compared to saturated fatty acids has been reported to be more competent in reducing the rate of fatty acid synthesis in the liver (12,19 It has been well demonstrated that dietary phospholipid decreases serum cholesterol concentration in the rat (1-3).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, precursors of F1P, such as fructose or sorbitol (16), are likely to be important for glucose clearance by liver after a meal. Indeed, supply of fructose together with glucose was shown to increase glycogen synthesis by liver in the rat and dog (32,33). Although fructose can be efficient to relieve hyperglycemia in diabetes, the use of fructose as a substituent for glucose for diabetes patients has raised the controversy (34,35).…”
Section: Discussionmentioning
confidence: 99%